Journey to Justice: The United Nations Declaration on the Rights of Indigenous Peoples in the Context of West Papua - Ani Widyani Soetjipto (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2022)
This article aimed to examine the implementation of the United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP), focusing on the rights of the Indigenous Papuan people in the Indonesian provinces on the western half of the island of New Guinea, commonly referred to in English as Papua or West Papua. By drawing on the theory of norm diffusion in the study of international relations, this article argues that despite adopting a declaration on the rights of indigenous peoples, the Indonesian government seems to find fulfilling the rights of Indigenous Papuans challenging due to obfuscation and lack of political will. This article finds that the implementation of special autonomy in Papua has been a failure, as the human rights situation has deteriorated and the fundamental rights of Indigenous Papuans remain unfulfilled.